The Analyzing Poverty Triggers in Central Java: HDI, Gini Ratio, and Unemployment (2011-2024) : Study on Central Java Across 2011-2024 - Yusuf, Maulana Ghani; Ramadhan, Muhammad Syah Fibrika (Kirana Publisher (KNPub), 2025)
Poverty remains a critical global challenge, central to the UN’s Sustainable Development Goals (SDGs), which aim to eradicate extreme poverty by 2030. This study examines the impact of the Human Development Index (HDI), unemployment, and income inequality (Gini Ratio) on poverty rates in Central Java (2011–2024) using quantitative methods. Time-series data from Indonesia’s Central Statistics Agency (BPS) were analyzed through multiple linear regression, preceded by classical assumption tests to ensure validity. Results indicate that HDI significantly reduces poverty, underscoring the importance of enhancing education, health, and living standards. However, unemployment and income inequality showed no statistically significant effects in this model, suggesting the need for deeper contextual analysis. These findings highlight the prioritization of HDI improvement in poverty alleviation strategies, while also considering complementary factors like infrastructure and social protection. The study contributes to SDG-oriented policymaking but recommends further research with expanded variables and broader samples to refine poverty reduction frameworks. By focusing on human capital development, Central Java can advance toward inclusive, sustainable poverty eradication.